Exploring the Impact of Emerging Diagnostic Methodologies on the Early Detection, Treatment, and Management of Infectious Diseases - Sajid, Bushra; Hameed, Aisha; Rafique, Saima; Nadeem, Amina; Niazi, Ammar; Haidar, Adeel (Journal of Neonatal Surgery, 2025)
Background: Emerging technologies in diagnostic procedures such as CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) systems, fast molecular testing, AI, met genomic sequencing, and others rapid tests keep on advancing the dynamic sphere of disease control and management. Their contemporaries are more difficult to diagnose and hence treated and hence reduces the quality of care. The new approaches are intended to maximize the results in terms of timely detection and identification of pathogens, resistance profiling, as well as enhanced system-level performances, which, in their turn, maintain the directed interventions in the area of public health. Objective: The aim of the study was to evaluate new diagnostic methods and their implications on clinical management and treatment of the infectious disease within a patient and population in terms of timeliness. Study Design: A prospective study at Jinnah Postgraduate Medical Centre (JPMC), tertiary care hospital in Karachi from Jan 2024 to September, 2024. Methods: The study was found to be prospective and carried out among patients who went to seek help in an infectious nature disease in a tertiary level care hospital. They have been discussed alongside the traditional culture based techniques with some new techniques like fast molecular evaluation and even of Meta genomic sequencing. Clinical data recorded, the duration of diagnostics, the duration to initiate treatment and a number of other patient outcomes. The precision by which these procedures were capable of calculation and the time and the clinical implications were also undertaken to do statistical analysis of the conventional techniques. Results: Finding was done in 100 patients. The mean age of respondents was 43.8 years and standard deviation of 12.6 years. Procedures diagnosed using new methods were in a significant position to identify more pathogens, 92 percent of the cases compared with the 68 percent which was diagnosed by conventional methods (p = 0.604). Novel methods including novel diagnostic procedures were significantly less time consuming (6.5 hours vs. 48 hours, p < 0.001). Sophisticated diagnostic techniques could reveal treatment at a lower stage of the illness to a much larger degree (84% versus 56% diagnosed using the traditional techniques p = 0.007). The clinical outcome was significantly improved in patients that had a reduction in hospital stay and reduction in ill placed broad spectrum antibiotics administered. Conclusion: The new diagnosis techniques possess the capacity to diagnose the problems earlier and thus the delays associated with diagnosis are minimized and the correct treatments commenced earlier. Their use does not only enhance patient health outcomes but also enhances antimicrobial stewardship and surveillance among the general population. Although such tools are relatively more expensive in the short term, they are proving to be of great value in the management of infectious diseases in the long term perspective. More remains to be done within the clinical environment in terms of workflow integration, as well as practical approaches to fairness and validation.